INTEGRASI NILAI ISLAM DALAM PEMBELAJARAN PENDIDIKAN SAINS (IPA) DI SEKOLAH DASAR NEGERI SADAMANTRA KUNINGAN - Pudin Saripudin (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2018)
AbstractThis study analyzes the relationship between science and religion in the view of Islam, and describes the integration between science and religion or science and technology in science learning activities (IPA) at Sadamantra State Elementary School, Jalaksana, Kuningan, West Java.This article confirms that the integration of Islamic values in science education education (IPA) at Sadamantra State Elementary School is real, done and so inevitably. This conclusion is contrary to the assumption that some scientists are doubting the integration of science and denying Islamic scholarship. The assumption that denying the integration of Islam and science is answered by the author by presenting normative, historical, and empirical evidence.The facts prove that the separation of religion with science will only complicate the learning process itself. After all, students must be equipped with Islamic values in science learning to stimulate student behavior as a learner as well as community in their environment.Keywords: Integration, Islamic values, Science, SDN Sadamantra AbstrakPenelitian ini menganalisis hubungan sains dan agama dalam pandangan Islam, dan mendeskripsikan integrasi antar sains dan agama atau iptek dan imtak dalam kegiatan pembelajaran sains (IPA) di Sekolah Dasar Negeri Sadamantra, Jalaksana, Kuningan, Jawa Barat.Artikel ini menegaskan bahwa integrasi nilai Islam dalam pembelajaran pendidikan sains (IPA) di Sekolah Dasar Negeri Sadamantra nyata, terlaksana dan sebau keniscayaan. Kesimpulan ini bertolak belakang dengan anggapan beberapa ilmuan yang menyangsikan integrasi keilmuan dan menafikan keilmuan Islam. Anggapan yang menafikan integrasi Islam dan sains dijawab oleh penulis dengan menghadirkan bukti-bukti normatif, historis, dan empiris.Fakta membuktikan bahwa pemisahan agama dengan sains hanya akan mempersulit proses pembelajaran itu sendiri. Bagaimana pun siswa harus dibekali dengan nilai-nilai keislaman dalam pembelajran IPA untuk memacu perilaku siswa sebagai pembelajar sekaligus komunitas di lingkungannya. Kata kunci: Integrasi, nilai-nilai Islam, Sains, SDN Sadamantra